3-D Shape measurement based on the unequal-period combination approach of phase coding and sinusoidal fringe. Issue 21 (15th December 2019) - Fu, Ling; Gao, Dingshan
ABSTRACT: The phase coding plus sinusoidal fringe method involves embedding the codeword into the phase domain, and is suitable for different contrast variation surfaces. However, as the number of phase coding fringe cycles increase, the fringe order becomes difficult to judge, ultimately leading to phase unwrapping errors. To resolve this issue, an unequal-period combination approach of phase coding and sinusoidal fringe was proposed. The main idea of this method was to project N cycles phase coding fringe, 2N (3N, 4N …) cycles sinusoidal fringe, and the phase coding fringe was ahead of the sinusoidal fringe. This method alleviated the difficulty in judging the fringe order and, consequently, improved measurement accuracy. Experiment results validated the efficiency and accuracy of this novel method.